2018
DOI: 10.7717/peerj.5200
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and molecular approximation to microbial niche: trophic interactions between oribatid mites and microfungi in an oligotrophic freshwater system

Abstract: Mite-fungal interactions play a key role in structuring core ecosystem processes such as nutrient dynamics. Despite their ecological relevance, these cross-kingdom interactions remain poorly understood particularly in extreme environments. Herein, we investigated feeding preferences of a novel genetic lineage of aquatic oribatids obtained from an oligotrophic freshwater system in the Cuatro Ciénegas Basin (CCB) within the Chihuahuan Desert, Mexico. During in vitro diet preference bioassays, transient aquatic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 110 publications
0
9
0
Order By: Relevance
“…We observed that T. churincensis sp. nov. reproduced differently on the three fungal species tested by Velez et al (2018), evident in the growth time of the different stages of development and the number of immature individuals in each of the treatments use. This fact, combined with its unspecialized feeding habits, may have allowed this species to endure through the extreme and fluctuating temperature and water chemistry conditions in the ponds and lagoons of the CCB.…”
Section: Parthenogenesis In T Churincensis Sp Novmentioning
confidence: 99%
See 3 more Smart Citations
“…We observed that T. churincensis sp. nov. reproduced differently on the three fungal species tested by Velez et al (2018), evident in the growth time of the different stages of development and the number of immature individuals in each of the treatments use. This fact, combined with its unspecialized feeding habits, may have allowed this species to endure through the extreme and fluctuating temperature and water chemistry conditions in the ponds and lagoons of the CCB.…”
Section: Parthenogenesis In T Churincensis Sp Novmentioning
confidence: 99%
“…Specimens of T. churincensis sp. nov. used in this study were obtained from several wood pine block submerged at the Laguna Intermedia of the Churince system in 2014-2015 (Cuatro Ciénegas Basin, Coahuila, Mexico; details see Velez et al 2018). Laboratory culture was started in November 2016 with 30 specimens for each block (total 5).…”
Section: Samplingmentioning
confidence: 99%
See 2 more Smart Citations
“…Micronutrients, on the other hand, correspond to elements called trace elements such as calcium, copper, iron, manganese, and zinc (Martín et al, 2019). Some fungi are considered oligotrophic, that is, they can survive in environments with a very limited supply of nutrients, growing in inhospitable environments, with high acidity and at temperatures above 37 ºC, acting in the capture of small amounts of volatile organic compounds of the atmosphere (Velez et al, 2018). Chemotrophs are fungi that need fixed forms of organic compounds, ranging from simple hexoses such as glucose to some types of polysaccharides such as starch and cellulose, as a means of supplying carbon and energy (Meena and Siddhardha, 2019).…”
Section: Introductionmentioning
confidence: 99%